Malignant hyperthermia – state of knowledge - Perszke, Michał; Egierska, Dominika; Cieślak, Kamil; Berliński, Miłosz; Świenc, Witold; Tokarczuk, Oskar; Walendzik, Anna (Journal of Education, Health and Sport, 2022)
Malignant hyperthermia (MH) is a relatively rare, but potentially lethal genetic disorder. That disease is characterized by hypermetabolic response of the skeletal muscles caused by exposure to triggering agents e.g. volatile anesthetics or depolarizing neuromuscular blockers. The object of this article was to review and assess the most recent published works about the epidemiology, etiology, pathomechanism, therapy of the MH and the new advances in all these fields. Authors scrutinized PubMed and Google Scholar using keywords: malignant hyperthermia, volatile anesthetics, ryanodine receptor mutation. In addition to this, the references of chosen articles were manually scoured for supplementary applicable articles. The literature was selected on the basis of a general medicine readership and prioritized clinical practice guidelines, systematic reviews and case reports. The references include the latest reports on malignant hyperthermia, apart from works of historical importance. Available treatment methods consist mainly of pharmacotherapy, symptomatic treatment and monitoring of vital parameters. Dantrolene is a first-choice drug in initial treatment of MH and is considered the only specific antidote. In spite of the constant advances in the areas of medicine there is still much to be discovered about MH. Further studies are necessary, as the amount of credible evidence is not adequate.